Effects of Illuminance Level of Light Source on White Appearance of a Tablet Display - Hsin-Pou Huang; Hung-Chung Li; Yu-Ming Fei; Minchen Wei (Applied Sciences, 2025)
The appearance of white significantly impacts display image quality, requiring a neutral white point for optimal performance. This study explores how perceived whiteness changes under ambient illumination levels (150, 300, 600, and 1200 lx) and correlated color temperatures (3500 K and 6500 K). As a result, the adapted white points of light sources with different correlated color temperatures are similar at lower ambient illuminance levels. In comparison, their adaptation trends exhibit significant differences at higher illuminance levels. At 150 lx, adapted white points for 3500 K and 6500 K light sources shift toward higher color temperatures and converge. With increased illumination, the 3500 K white point shifts toward its light source, while the 6500 K white point shifts to a higher correlated color temperature. The neural network-based prediction model developed in this study accurately forecasts perceived whiteness across conditions, offering valuable design guidance for the display and lighting industries.